2016
DOI: 10.1371/journal.pone.0154055
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Exosomal microRNA-451-5p Is a Potential Early Biomarker of Diabetic Nephropathy in Rats

Abstract: Non-invasive renal signatures can help in serial monitoring of diabetic patients. We tested whether urinary exosomal (UE) microRNA (miR) analysis could non-invasively predict renal pathology in diabetic rats during the course of diabetes. Diabetes mellitus (DM) was induced in male Wistar rats by a single intraperitoneal injection of streptozotocin (STZ, 50 mg/kg body weight). Non-diabetic control (CTRL) rats were injected with vehicle. Insulin (INS) treatment (5U/d, s.c.) was provided to 50% of the DM rats. Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 56 publications
2
65
0
Order By: Relevance
“…Thirdly, in some cases, miRNA changes expression level in the early stage of DN, which related to fibrosis [62]. For example, Mohan et al reported that miR-451-5p and miR-16 in diabetes appeared to be protective against diabetes-induced kidney fibrosis, while UE miR-451-5p may hold prognostic value as an early and sensitive noninvasive indicator of renal disease [63]. Similar to miRNA, lncRNA also can help in serial monitoring of diabetic patients.…”
Section: Epigenetic and Ncrna-based Therapymentioning
confidence: 99%
“…Thirdly, in some cases, miRNA changes expression level in the early stage of DN, which related to fibrosis [62]. For example, Mohan et al reported that miR-451-5p and miR-16 in diabetes appeared to be protective against diabetes-induced kidney fibrosis, while UE miR-451-5p may hold prognostic value as an early and sensitive noninvasive indicator of renal disease [63]. Similar to miRNA, lncRNA also can help in serial monitoring of diabetic patients.…”
Section: Epigenetic and Ncrna-based Therapymentioning
confidence: 99%
“…Urinary exosomes were isolated from rat and human urine samples by ultracentrifugation and characterized as previously described by us (Kalani et al, 2013;Mohan et al, 2016).…”
Section: Urinary Exosomes Isolation and Characterizationmentioning
confidence: 99%
“…Besides its widely known dysregulation in malignancies, its overexpression in human coronary artery disease is now well appreciated (Zhang et al, 2010). With regards to kidney disease, dysregulation of miR-451 has been reported in human patients with DN and in mouse models of DN associated with mesangial hypertrophy (Wei et al, 2013;Mohan et al, 2016;Sun et al, 2016). In the previous study from our laboratory, we found a rise in miR-451 expression in uEs from diabetic rats as early as 6 weeks postdiabetes induction, and its levels continued to increase with disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA‑29 levels in urine exosomes have been proposed as a biomarker of kidney fibrosis but their expression can be dynamic. In a recent study, Mohan et al reported that urinary exosomal miRNA‐451‐5p level was increased in diabetic rats 3 weeks prior to significant albuminuria and 3 weeks before histological changes of kidney fibrosis. In contrast, renal expression of miRNA‐451‐5p declined and was negatively associated with the indices of renal pathology during the progression of DKD.…”
Section: Quantification Of Urinary Mirnas As Biomarkers For Dkdmentioning
confidence: 99%